Description of novel members of the family Sphingomonadaceae: Aquisediminimonas profunda gen. nov., sp. nov., and Aquisediminimonas sediminicola sp. nov., isolated from freshwater sediment. Issue 8 (17th June 2019) - Jin, Long; Ko, So-Ra; Jin, Chun-Zhi; Jin, Feng-Jie; Li, Taihua; Ahn, Chi-Yong; Oh, Hee-Mock; Lee, Hyung-Gwan
Abstract : Two Gram-stain-negative bacterial strains, DS48-3 T and CH68-4 T, were isolated from freshwater sediment taken from the Daechung Reservoir, Republic of Korea. Cells of strains DS48-3 T and CH68-4 T were aerobic, non-motile, non-spore-forming and rod-shaped. Strain DS48-3 T was isolated from a sediment surface sample at a depth of 48 m from the Daechung Reservoir and was most closely related to the genus Sphingopyxis according to 16S rRNA gene sequence analysis (94.5–95.9 % similarity). Strain CH68-4 T was isolated from the very bottom of a 67-cm-long sediment core collected from Daechung Reservoir at a water depth of 17 m and was most closely related to the genus Sphingopyxis (16S rRNA gene sequence similarity of 93.7–95.0 %). Phylogenetic analysis based on 16S rRNA gene sequencing indicated that the two strains formed a separate lineage within the order Sphingomonadales showing similarity values below 95.9 % with their closest phylogenetic neighbours, and sharing 97.3 % similarity with each other. The combined genotypic and phenotypic data showed that strains DS48-3 T and CH68-4 T could be distinguished from all genera within the family Sphingomonadaceae and represented two distinct species of a novel genus, Aquisediminimonas profunda gen. nov., sp. nov. (type strain DS48-3 T =KCTC 52068 T =CCTCC AB 2018061 T ) and Aquisediminimonas sediminicola sp. nov. (type strain CH68-4 T =KCTC 62205 T =CCTCC AB 2018062 T ).